Managing Large-Scale Software Projects using Features of Agile Methods - Hanafi Riyadh Alfayomi (International Journal of Computers and Informatics, 2025)
Software is a part of all aspects of our lives, and organizations are increasingly conceiving extremely large and complex software projects. The software industry has an option to choose suitable methodology/process model for its current needs to provide solutions to give problems. According to some researchers, a hybrid approach can help optimize the software development lifecycle by combining two or more methodologies. eXtreme Programming (XP) and Scrum are most widely practiced and documented agile models. Both XP and scrum work well for small projects whereas Rational Unified Process (RUP) is suitable for large projects. This paper analyzes characteristics, strengths, and weaknesses of both conventional and agile methods. This paper also explains the four major phases and nine disciplines of the RUP, XP, and the common elements of the Scrum process. Finally, this paper suggests a new hybrid software development method that combines the RUP with XP and Scrum processes to accommodate the strengths of both methods while suppressing their weaknesses to get high quality and improve team productivity. The hybrid method can be utilized in the software industry, particularly in the business sectors that deal with large-scale software projects.
Keywords: Traditional Development Methodologies; Agile Development Methodologies; Large Scale Software Projects